Photoluminescence at room temperature in disordered Ba(0.50)Sr(0.)5(0)(Ti0.80Sn0.20)O-3 thin films - Souza, I. A.; Simoes, A. Z.; Longo, Elson [UNESP]; Varela, José Arana [UNESP]; Pizani, P. S. (American Institute of Physics (AIP), 2006)
Photoluminescence (PL) properties at room temperature of disordered Ba0.50Sr0.50(Ti0.80Sn0.20)O-3 (BST:Sn) thin films were obtained by the polymeric precursor method. X-ray diffraction data and corresponding PL properties have been measured using the 488 nm line of an argon ion laser. The PL spectra of the film annealed at 350 degrees C for 21 h are stronger than those of the film annealed at 350 degrees C for 28 h, indicating a disorganized structure. The energy band gaps of the crystalline and amorphous BST:Sn thin films were 3.35 and 2.25 eV, respectively. The doped BST thin films also tend to a cubic structure, resulting from TiO6 deformations. (c) 2006 American Institute of Physics.